THE INFLUENCE OF AWARENESS AND UNDERSTANDING OF PHILIPPINE VAPING LAW IN ADOLESCENT E-CIGARETTE USE - Constantino, Rowena M. (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Vaping prevalence in adolescents has been a public health concern worldwide. Despite implementation of vaping laws aimed at curbing this increasing menace, vaping still continues to rise. The aim of this study is to identify gaps in vaping regulations by identifying the factors, attitudes and beliefs, awareness of health risks, awareness of Philippine vaping law and compare the regulation provisions of ASEAN countries. This research employs analytical cross-sectional study with benchmarking component utilizing survey questionnaires answered by participants through Google forms. Results revealed that factors on personal, social, psychological and environmental play a role in the increasing vaping use in adolescents. Participants answered positively on the attitude and belief, knowledge on the impacts of vaping and possible interventions. Most of the participants lack awareness of the provisions of the Vape law. The Philippines, despite a comprehensive vaping law, still has the highest prevalence rate among the ASEAN countries. In conclusion, several factors influenced the increasing prevalence of vape in the Philippines and this can be addressed by strictly enforcing or amending some of the provisions of the law. For the recommendation, multi-sectoral involvement and strategies are needed to decrease the prevalence of vaping in the Philippines.